2018
DOI: 10.1002/jpln.201700455
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient use efficiency and harvest index of cassava decline as fertigation solution concentration increases

Abstract: Response of cassava (Manihot esculenta Crantz) to fertigation as a form of nutrient delivery is unknown. The objectives of this study were to establish a balanced nutrition and to enhance agronomic nutrient use efficiency (ANUE) of cassava under fertigation. This study was conducted in the greenhouse and in the field. In both, the results showed a similar trend. There were six fertigation concentrations and three cassava varieties, selected for their duration of growth in the field. Shoot biomass of the long‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Potassium accumulation in the leaves, as cassava develops, is an indication of its continuous requirement for various plant functions, especially root formation and development in root crops (Howeler , Wang et al ). Although the analysis of K in the leaf ends at 88 days after treatment, which is far below the cassava harvesting dates in most farmers' fields, it is 28 days after initiation of storage root bulking (Alves ) and within the range when significant root yield was observed in another cassava fertigation experiment (Omondi et al ). It is noteworthy to state that the time of initiation of storage root bulking could be variable depending on variety, management and climate; nonetheless, according to reviewed literature, only Alves () documented the range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium accumulation in the leaves, as cassava develops, is an indication of its continuous requirement for various plant functions, especially root formation and development in root crops (Howeler , Wang et al ). Although the analysis of K in the leaf ends at 88 days after treatment, which is far below the cassava harvesting dates in most farmers' fields, it is 28 days after initiation of storage root bulking (Alves ) and within the range when significant root yield was observed in another cassava fertigation experiment (Omondi et al ). It is noteworthy to state that the time of initiation of storage root bulking could be variable depending on variety, management and climate; nonetheless, according to reviewed literature, only Alves () documented the range.…”
Section: Discussionmentioning
confidence: 99%
“…In these greenhouse experiments, 30‐cm cuttings with six nodes of an Israeli cassava variety (donated by a farmer who has planted it in Asqelon‐Israel for 30 years, the origin is unknown, but the morphological traits were described in Omondi et al ) were planted in 2‐l pots filled with tap water‐saturated 6‐mm perlite granules, i.e. high porosity, high hydraulic conductivity, and minimum interaction with nutrients (Erel et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient use efficiency, e.g., the amount of biomass produced per K unit supplied, is a valued tool for evaluating the ability of the plant to utilize environmental inputs into yield or biomass production (Yasuor et al, 2013; Omondi et al, 2018). We report here for medical cannabis, a large decrease in KUE with the increase in K supply ( Figure 1D ).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in Cassava Yield per Area by Fertilizer Application DOI: http://dx.doi.org/10.5772/intechopen.97366 are variations in the levels of advantage due to different factors such as variety response, agro-ecological zones characteristics, agronomic and crop management practices etc. For example, under fertigation (application of fertilizers or other soil amendments intended to improve soil fertility through an irrigation system) in [14] study, all the cassava varieties receive similar treatments yet the fertilizer advantage is different -Kamplombo variety responding better to fertilizer application.…”
Section: Cassava Root Yield Under Fertigation and Bandingmentioning
confidence: 92%
“…Interestingly, it has been observed that cassava root yield increase with fertilizer application even in Sub-Saharan Africa [11][12][13]. Recent studies on the effects of fertigation on growth and root yield of cassava, Omondi et al [14] established fertigation concentrations at which maximum storage root yields were achieved in the field for three cassava varieties (Mweru, Nalumino and Kampolombo).…”
Section: Introductionmentioning
confidence: 99%